Impact and cost‐effectiveness of the national scale‐up of HIV pre‐exposure prophylaxis among female sex workers in South Africa: a modelling analysis. Issue 2 (20th February 2023) - Stone, Jack; Bothma, Rutendo; Gomez, Gabriela B.; Eakle, Robyn; Mukandavire, Christinah; Subedar, Hasina; Fraser, Hannah; Boily, Marie‐Claude; Schwartz, Sheree; Coetzee, Jenny; Otwombe, Kennedy; Milovanovic, Minja; et al.
Abstract: Introduction: In 2016, South Africa (SA) initiated a national programme to scale‐up pre‐exposure prophylaxis (PrEP) among female sex workers (FSWs), with ∼20, 000 PrEP initiations among FSWs (∼14% of FSW) by 2020. We evaluated the impact and cost‐effectiveness of this programme, including future scale‐up scenarios and the potential detrimental impact of the COVID‐19 pandemic. Methods: A compartmental HIV transmission model for SA was adapted to include PrEP. Using estimates on self‐reported PrEP adherence from a national study of FSW (67.7%) and the Treatment and Prevention for FSWs (TAPS) PrEP demonstration study in SA (80.8%), we down‐adjusted TAPS estimates for the proportion of FSWs with detectable drug levels (adjusted range: 38.0–70.4%). The model stratified FSW by low (undetectable drug; 0% efficacy) and high adherence (detectable drug; 79.9%; 95% CI: 67.2–87.6% efficacy). FSWs can transition between adherence levels, with lower loss‐to‐follow‐up among highly adherent FSWs (aHR: 0.58; 95% CI: 0.40–0.85; TAPS data). The model was calibrated to monthly data on the national scale‐up of PrEP among FSWs over 2016–2020, including reductions in PrEP initiations during 2020. The model projected the impact of the current programme (2016–2020) and the future impact (2021–2040) at current coverage or if initiation and/or retention are doubled. Using published cost data, we assessed the cost‐effectiveness (healthcare provider perspective; 3% discount rate; time horizon 2016–2040) of the current PrEP provision. Results: Calibrated to national data, model projections suggest that 2.1% of HIV‐negative FSWs were currently on PrEP in 2020, with PrEP preventing 0.45% (95% credibility interval, 0.35–0.57%) of HIV infections among FSWs over 2016–2020 or 605 (444–840) infections overall. Reductions in PrEP initiations in 2020 possibly reduced infections averted by 18.57% (13.99–23.29). PrEP is cost‐saving, with 1.42 (1.03–1.99) of ART costs saved per dollar spent on PrEP. Going forward, existing coverage of PrEP will avert 5, 635 (3, 572–9, 036) infections by 2040. However, if PrEP initiation and retention doubles, then PrEP coverage increases to 9.9% (8.7–11.6%) and impact increases 4.3 times with 24, 114 (15, 308–38, 107) infections averted by 2040. Conclusions: Our findings advocate for the expansion of PrEP to FSWs throughout SA to maximize its impact. This should include strategies to optimize retention and should target women in contact with FSW services.